Pengembangan Karier Terhadap Kepuasan Kerja Melalui Self Efficacy Pada PT. PLN ULP - Rasmiyati, mery Icha; Noer, Elly; Betaubun, Sopia (EKONOMI & SOSIAL, 2023)
The purpose of this study to learn the effect that career development can have on the satisfaction of work through self indulgence acy asan intering variable. The study is a quantitative approach with the sample taking technique using a total sampling of as many as 36 respondents who represent all pt. PLN ulp kurik employees. The source of data used in the study is primary and secondary data. The data-collection techniques used are observation, interviews, installations or questionnaires and documentaries. Data are processed using analysis techniques using research instruments (validity tests and recapabilities tests) and using stream analysis aided by statistical product and service solutions (SPSS). Research indicates (1) career development affects job satisfaction, (2) career development affects self literacy, (3) self advoacy affects work satisfaction, (4) career development affects work satisfaction through self literacy. The magnitude of the influence variable career development and self acy have on greater job satisfaction but there are still some other variables affecting the variables of job satisfaction